GIS IN URBAN GEOLOGY: THE CASE STUDY OF NAFPLIO, ARGOLIS PREFECTURE, GREECE - Zervakou, A.D.; Tsombos, P. (Bulletin of the Geological Society of Greece, 2010)
The aggregation of population in big cities leads to the concentration of human activities, overconsumption of natural resources and urban growth without spatial planning and sustainable management. As a result, urban societies are exposed to various dangers and threats with economic, social, ecological, and environmental impacts on the urban surroundings. Problems associated with urban development are related to the existing geological conditions. Therefore, the provision of appropriate geological information about the urban environment is essential for every sustainable urban planning. The first systematic recording, codification and documentation of “Urban Geology” geothematic information in Greece was implemented by the Institute of Geology and Mineral Exploration (I.G.M.E.) in the framework of the project called “Collection, codification and documentation of geothematic information for urban and suburban areas in Greece - pilot applications”. Through the implementation of this project, geological mapping, geotechnical, geochemical, geophysical research and measurements took place at four pilot cities of Greece. Nafplio, the capital city of Argolis prefecture, was one of them. During the project, all compiled data were stored and processed in specially designed geodatabases in GIS environment in order to produce multifunctional geothematic maps and other digital products (DEMs, 2D - 3D surfaces).